2015
DOI: 10.1093/iwc/iwu050
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework for Evaluating Intuitive Interaction Based on Image Schemas

Abstract: Intuitive interaction is an important aspect of usability in interface design. This paper contributes to the research in this area by proposing a conceptual framework for evaluating intuitive interaction based on image schemas. The framework comprises four phases: goal identification, image schemas extraction, analysis, and assessment. It quantifies intuitive interaction by comparing the image schemas envisaged by the designer of a product with those used by its users. The proposed framework is evaluated throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Hurtienne et al [10] proposed designing intuitive tangible user interfaces with the help of 'image schemas' and their metaphorical extensions. Also, Asikhia et al [11] had reported an approach for quantitatively evaluating the affective aspect or intuitive interaction. Also, similar to our exploration, Blackler et al [12] had attempted to explore the notion of the intuitive use of the product and how to design for the same.…”
Section: Related Researchmentioning
confidence: 99%
“…Hurtienne et al [10] proposed designing intuitive tangible user interfaces with the help of 'image schemas' and their metaphorical extensions. Also, Asikhia et al [11] had reported an approach for quantitatively evaluating the affective aspect or intuitive interaction. Also, similar to our exploration, Blackler et al [12] had attempted to explore the notion of the intuitive use of the product and how to design for the same.…”
Section: Related Researchmentioning
confidence: 99%
“…Recently, the use of image schemas has been proposed as a means for exploring intuitive interaction [7], [8]. Image schemas are defined as mental patterns that structure human experiences in the world [9].…”
Section: Introductionmentioning
confidence: 99%
“…Balancing these high functional expectations and the correct interpretation of the product features by consumers are often difficult to meet when several technologies are located in the same device (Asikhia et al, 2015). For example, mobile phones have been equipped with different functionality comprising games, cameras and various softwares.…”
Section: Introductionmentioning
confidence: 99%